Cloning and Transcriptional Activity Analysis of the Porcine Abcb1 Gene Promoter: Transcription Factor Sp1 Regulates the Expression of Porcine Abcb1 - Guo, Tingting; Huang, Jinhu; Huan, Changchao; He, Fang; Zhang, Yujuan; Bhutto, Zohaib A.; Wang, Liping (Frontiers in Pharmacology, 2018)
P-glycoprotein (P-gp, Abcb1) plays a crucial role in drug disposition and exerts its effects by hydrolyzing ATP. However, little is known about the regulatory elements governing the transcription of porcine Abcb1 gene. In this study, the transcription start site (TSS) was firstly identified by 5′-RACE. A 1.9-kb fragment of the 5′ flanking region of Abcb1 gene from pig genomic DNA was firstly cloned and sequenced. The region in Abcb1 promoter which is critical for promoter activity was investigated via progressive deletions. Further, using mutation assay, two proximal Sp1 binding sites within the 5′-flanking region of Abcb1 were proved to be important cis-regulatory elements involved in regulating the constitutive expression of procine Abcb1. RNA interference experiments showed that Sp1 could regulate the expression of the porcine P-gp at both mRNA and protein level. Hence, the current work will contribute valuable information to understanding the molecular regulatory mechanisms of pig Abcb1.